Estimation of biomass and carbon stored in trees in the Sisimeni Sanam Forest Area, Timor Island, Indonesia - FRANSISKUS XAVERIUS DAKO; FLORA EVALINA INA KLERUK; FRENLY M. SELANO; KLETUS F. S. GARE; HABEL M. NOPEMNANU (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Dako FX, Kleruk FEI, Selanno FM, Gare KFS, Nopemnanu HM. 2025. Estimation of biomass and carbon stored in trees in the Sisimeni Sanam Forest Area, Timor Island, Indonesia. Biodiversitas 26: 5324-5333. Forests are crucial in human life, particularly in preventing global warming caused by climate change. The Sisimeni Sanam Forest Area, located in the western part of Timor Island, Indonesia, contributes significantly to climate regulation and hence requires proper management. This study quantified above-ground biomass, carbon stock, and CO? sequestration in Sisimeni Sanam to provide a baseline for conservation and climate mitigation strategies. Systematic sampling was applied in the field using the Line Plot method. With a sampling intensity of 1%, the total sampled area covered 4.97 ha. A total of 124 measurement plots, each measuring 20 × 20 meters, were established to assess biomass potential and carbon reserves. The analyses showed content, total carbon reserves, and carbon sequestration of 815.73 tons/ha, 383.39 tons/ha, and 1,200.08 tons/ha, respectively. The type of vegetation with the highest biomass, carbon reserves, and carbon sequestration is teak (Tectona grandis), with 249.79 tons/ha, 117.40 tons/ha, and 430.86 tons/ha, respectively. In contrast, pulai (Alstonia scholaris) recorded the lowest values, at 4.07 tons/ha, 1.91 tons/ha, and 7.01 tons/ha, respectively. These results indicate that Sisimeni Sanam functions as a significant carbon reservoir within Timor's dry tropical landscape. Therefore, maintenance and preservation of the area are needed for proper functioning as a carbon absorber rather than a producer.